(untitled) (Emancipação, 2017)
This study analyzes whether the National School Meal Program (NSMP), through the participation of family farming, had relation with the economic, environmental and social dimensions of sustainable development, and also verify if the traditional communities access it. It is an exploratory, descriptive, qualitative and quantitative study carried out in the Southwest Paraná. Effectively, 24 (57%) municipalities participated in this research. It was found that, between 2011 and 2015, 18 reached the average acquisition of family agriculture for school meal required by law, however, only 01 they got certified organic products and, on average, just over 2% of family farmers participated in the implementation of NSMP . There was no acquisition of traditional peoples in any of the 04 municipalities where these communities are located. It was observed that public policy is relevant, however, although the improvements observed in the percentage of purchase, its operationalization is not yet complete, requiring improvement and consolidation, including the inclusion of traditional communities in its implementation.